2022
DOI: 10.3390/cancers14041034
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon–Pathologist Team Approach Dramatically Affects Lymph Nodes Detection and Improves Patients’ Short-Term Outcome

Abstract: The downstaging of gastric cancer has recently gained particular attention in the field of gastric cancer surgery. The phenomenon is mainly due to an inappropriate sampling of lymph nodes during standard lymphadenectomy. Hence, collection of the maximum number of lymph nodes is a critical factor affecting the outcome of patients. None of the techniques proposed so far have demonstrated a real efficiency in increasing the number of identified lymph nodes. To harvest the maximum number of lymph nodes, we designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…In Japan, surgeons themselves separate lymph nodes from the excised specimen, map them according to each lymph node station and then submit it for pathological examination. Ambrosio et al ( 10 ) compared the Japanese method (surgeons and pathologists working together to identify lymph nodes at each station) with the conventional method (the resected specimen is fixed in formalin and the pathologist identifies the lymph nodes) for resected gastric cancer specimens. The results showed that the Japanese method retrieved significantly more lymph nodes than the conventional method (79 vs. 29, P=0.001).…”
mentioning
confidence: 99%
“…In Japan, surgeons themselves separate lymph nodes from the excised specimen, map them according to each lymph node station and then submit it for pathological examination. Ambrosio et al ( 10 ) compared the Japanese method (surgeons and pathologists working together to identify lymph nodes at each station) with the conventional method (the resected specimen is fixed in formalin and the pathologist identifies the lymph nodes) for resected gastric cancer specimens. The results showed that the Japanese method retrieved significantly more lymph nodes than the conventional method (79 vs. 29, P=0.001).…”
mentioning
confidence: 99%